Water utility efficiency assessment in Italy by accounting for service quality: An empirical investigation. (April 2017) - Romano, Giulia; Molinos-Senante, María; Guerrini, Andrea
Abstract: In Italy's water industry, publicly owned utilities (PWCs) coexist with public-private partnerships (PPPWCs), that could contribute expertise for operations, funds, and relationships. This paper examines the effect of ownership structures on efficiency by comparing Veneto (with almost all PWCs) and Tuscany (with almost all PPPWCs). This comparison is highly debated, with possible economic, social, environmental, and political implications. A Data Envelopment Analysis approach, that uses both quantitative and qualitative variables to represent the lack of service quality, was adopted. Results suggest that PWCs perform slightly better when quality issues are excluded, while PPPWCs perform better when considering both variable types. Highlights: Quality is usually omitted in the study of the performance of water utilities. Quantity-only measures penalize utilities that produce higher quality services. The performance difference represents the opportunity cost of maintaining quality. Public entities perform slightly better when quality issues are excluded. Public-private partnerships perform better when quantity and quality are considered.